2021
DOI: 10.3233/sfc-210273
|View full text |Cite
|
Sign up to set email alerts
|

Level Set function-based Functionally Graded Material for the reduction of maximum stresses around a pair of inclined unequal circular holes

Abstract: OBJECTIVE: The aim of this work is to present the methodology for grading the Functionally Graded Material (FGM) using Level Set (LS) sign distance function around the multiple holes and parametrically analyse the maximum stresses for a pair of inclined unequal circular holes surrounded by the FGM layer in an infinite plate subjected to uniaxial tensile load using the Extended Finite Element Method (XFEM). METHODS: The LS method has the ability to represent the multiple geometrical boundaries with a single sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…FGM layer around the discontinuity is one of the approaches which can reduce property mismatch and avoid stress concentration. FGM is a composite material concept consisting of varying volume fractions of its constituents that result in smooth variation in material properties along the direction of gradation (Goyat et al, 2021). Luo and Gao (2009) solved the stress analysis problem of arbitrary inclusion using complex variable method and Faber-Laurent series.…”
Section: Introductionmentioning
confidence: 99%
“…FGM layer around the discontinuity is one of the approaches which can reduce property mismatch and avoid stress concentration. FGM is a composite material concept consisting of varying volume fractions of its constituents that result in smooth variation in material properties along the direction of gradation (Goyat et al, 2021). Luo and Gao (2009) solved the stress analysis problem of arbitrary inclusion using complex variable method and Faber-Laurent series.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2021) experimentally investigated the stress concentration reduction for a circular hole with FGM layer and observed that the experimental results have good agreement with theoretical results. Goyat et al (2021) analyzed the SCF reduction and optimized the parameters of level set based FGM for inclined pair of circular holes.…”
Section: Introductionmentioning
confidence: 99%